Association between health-related quality of life and menopausal status and symptoms in women living with HIV aged 45–60 years in England: An analysis of the PRIME study. (January 2022) - Okhai, Hajra; Dragomir, Livia; Pool, Erica RM; Sabin, Caroline A; Miners, Alec; Sherr, Lorraine; Haag, Katharina; Dhairyawan, Rageshri; Vora, Nina; Sultan, Binta; Gilson, Richard; Burns, Fiona; et al.
Objectives: The aim of this study was to compare the health-related quality of life between mid-life women with HIV and the general population and to investigate the association between health-related quality of life and menopausal (1) status and (2) symptoms among women with HIV. Methods: Cross-sectional data of women with HIV aged 45–60 years from the Positive Transitions Through the Menopause Study. Health-related quality of life was assessed using the Euroqol questionnaire with utility scores categorizing health as perfect (score = 1.00), sub-optimal (0.75–0.99) or poor (< 0.75). Scores were compared between Positive Transitions Through the Menopause study participants and women (aged 45–59 years) from the Health Survey for England. Associations between health-related quality of life and menopausal status/symptoms in Positive Transitions Through the Menopause participants were assessed using a multivariable two-part regression model, the results of which are combined to produce a single marginal effect. Results: In total, 813 women from the Positive Transitions Through the Menopause study were included (median age 49 (interquartile range: 47–53) years); the majority were of Black African ethnicity (72.2%). Overall, 20.9%, 43.7% and 35.3% of women were pre-, peri- and post-menopausal, respectively, and 69.7% experienced mild/moderate/severe menopausal symptoms. Approximately, 40% reported perfect health, 22.1% sub-optimal health and 39.0% poor health, similar to women from the Health Survey for England (perfect health: 36.9%, sub-optimal health: 25.2%, poor health: 37.9%). In multivariable models, we found an association between health-related quality of life and peri-menopausal status (marginal effect: 0.07 (0.02, 0.12)); however, the association with post-menopausal status was attenuated (marginal effect: 0.01 (–0.05, 0.06)). There remained a strong association between lower utility scores and moderate (marginal effect: 0.16 (0.11, 0.20)) and severe (marginal effect: 0.32 (0.27, 0.39)) menopausal symptoms. Conclusion: There were no differences in health-related quality of life between women with HIV (Positive Transitions Through the Menopause participants) and women from the Health Survey for England dataset. Among Positive Transitions Through the Menopause participants, health-related quality of life was reduced in peri-menopausal women and those with increasingly severe menopausal symptoms. Our findings highlight the importance of proactive assessment of menopausal status and symptoms to optimize health-related quality of life in women living with HIV as they reach mid-life and beyond.